Effects of ageing on bioavailability of selenium in soils assessed by diffusive gradients in thin-films and sequential extraction - Peng, Qin; Li, Jun; Wang, Dan; Wei, Tian-Jiao; Chen, Chang-Er L.; Liang, Dong-Li (Plant and soil, 2019)
Background and aims Ageing is an important factor for controlling selenium bioavailability and toxicity in soil. Methods The ageing processes of selenite and selenate in two soils were systematically investigated by adopting diffusive gradients in thin film technique (DGT) and sequential extraction. Results Soluble Se was the main fraction (29.3%–61.7%) for selenate-treated soils, and which decreased significantly (52.5% for chestnut soil and 44.2% for black soil) and transformed to less labile fractions with ageing. By contrast, exchangeable Se fraction was the main fraction in selenite-treated soils, which decreased by 38%–71.8% with ageing. The DGT measurement ( C DGT ) of selenate treatment was 1.8–96.7 times higher than that of selenite treatment. Dynamic analysis showed that shorter response time T c (44 s) and higher desorption rate constant k −1 (≥ 1.5E-3 s −1 ) were observed in selenite-treated chestnut soil than black soil, which coincided with the higher Se contents in pak choi planted in chestnut soil than black soil. The opposite result was found for selenate, demonstrating that Se bioavailability was affected by soil properties and Se species. Conclusions This study demonstrated that DGT can describe the changes of Se bioavailability caused by ageing and predict Se uptake by pak choi roots in selenite- or selenate-aged soils.